Operational methods of estimating the current functional sportsman's state in the system of training process - Yaroslavna Puhach; Natalya Pashchenko; Tamara Lyakhova (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to develop the methodology for an individual assessment of the current functional state when organizing the training process. Materials and methods: the following methods were used: analysis and generalization of scientific and methodological literature; generalization of the experience of the practical work of the coaching contingent working with the contingent of sports improvement groups in basketball; methods of mathematical modeling and processing of video materials of sports competitions of various levels in basketball; the modernized method of orthostatic test by N. Teslenko - test «sitting-standing". Results: an individual method for assessing the functional state in the process of conducting the training lesson allows to determine the measure of working capacity and the athlete's readiness to the loads presented. The practically developed method makes it possible to introduce control over the state of developed fatigue in real time, thereby assessing the level of performance and giving objective assessments of individual endurance. In practice, the developed method makes it possible to introduce control over the state of developing fatigue in real time, thereby assessing the level of performance and giving objective assessments of individual endurance. It should be noted that the modified method of N. Teslenko orthostatic test with the use of modern computer technology makes it possible to transmit the information received at any distance and control the state of the athlete's body without restricting his motor activity. Conclusions: the developed technique of the modified orthostatic test by N. Teslenko allows early diagnosis of the development of fatigue, which prevents the deterioration of the body and prevents the phenomena of fatigue.